Musāhamātu ‘Ulamā’i al Hindi fī al Ṣaḥāfati al “Arabiyyat: Dirāsatun Waṣfiyyatun ‘an Ṡalāṡati Minhum - bin Shah al-Hamid, Muhammad Saifullah; Ansari, Abdul Rashid bin (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
The media play an important role in providing investigative reports, discussions, social background, political analysis, and news that show the realities of society. One of the most important means of human communication in the world is the press. A free press is important because if the media are able to report events truthfully, important information may be withheld and voters will remain in the dark. Likewise, if the media is not allowed to facilitate open and free discussion, then the opinions and concerns of ordinary people will not be heard. It is for this interest that Indian scholars pay attention to strong practices in the field of journalism. Mainly, they are doing their best for the Arab press across India. It is this leading personality. Sheikh Al-Sayyid Muhammad Wahid Rashid Al-Nadawi, Sheikh Dr. Mohiuddin Al-Alawi, and Sheikh Dr. Saeed Al-Rahman Al-Azami, who works in public broadcasting and translates several books from English to Arabic, and they have a prominent role in the field of modern Arab-Indian journalism. And a strong memory, as evidenced by hundreds of pages of magazines, magazines and books, in which he still writes and touches on these issues related to religion, morals, language, politics and culture, uniting the old and the new.